2022
DOI: 10.1051/rees/2021050
|View full text |Cite
|
Sign up to set email alerts
|

The impact of efficient insulation on thermal performance of building elements in hot arid region

Abstract: The application of thermal insulation technique for buildings in hot arid region still under development and requires investigation for many aspects, especially those related to the individual elements of the construction. The present study investigates the impact of efficient insulation on the thermal performance of the following construction elements: wall, roof and foundation. The techniques used for the insulation have followed the Passive House criteria. The study introduces many benefits for passive desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…Hence, treating roof with layer of insulation is one of the good options, and in this The small-scale building treatments with additional of green roof as insulation layers has the potential to reduce solar radiation as reported by the previous study. This study reported that the material with higher thermal resistance, R-value, will radiates less heat into indoor buildings [38]. Figure 9 depicts the R-values, with the red contour indicating area with the highest R-value, and dark blue contour with the lowest.…”
Section: Figure 6 Simulation Of Building Orientationmentioning
confidence: 96%
“…Hence, treating roof with layer of insulation is one of the good options, and in this The small-scale building treatments with additional of green roof as insulation layers has the potential to reduce solar radiation as reported by the previous study. This study reported that the material with higher thermal resistance, R-value, will radiates less heat into indoor buildings [38]. Figure 9 depicts the R-values, with the red contour indicating area with the highest R-value, and dark blue contour with the lowest.…”
Section: Figure 6 Simulation Of Building Orientationmentioning
confidence: 96%
“…2 A prior study has explored the thermal performance of insulation panels for construction applications in hot, dry climates, but this research is still in its infancy and has to be expanded in several ways. 3,4 The use of adequate insulation panels in the building envelope is one of the most efficient techniques to minimize the rate of heat transmission and energy consumption to cool and heat buildings. 5 The most common examples of insulation panels used in tropical climate countries are polystyrene panels 6 and gypsum panels.…”
Section: Introductionmentioning
confidence: 99%